Clinical Correlation Between Immunohistochemistry Markers And Neuronal Dysfunction In Anorectal Malformations And Hirschsprung Disease Patients - milankumar, milankumar; kansal , Sandeep; gyanendra, gyanendra (Journal of Neonatal Surgery, 2025)
Introduction: Congenital colorectal disorders like Hirschsprung disease (HD) and anorectal malformations (ARM) significantly contribute to pediatric morbidity and mortality. Accurate diagnosis of these disorders, particularly HD, often hinges on histopathological evaluation. Hematoxylin and Eosin (H&E) staining is the traditional diagnostic tool, though it has limitations due to the variable distribution and subtle appearance of ganglion cells, especially in neonates. Material and Methods: This cross-sectional study was conducted in the Department of General Surgery at CSSH Medical College from July 2023 to February 2025, including 20 clinically diagnosed cases of HD and ARM. Ethical clearance was obtained, and informed consent was secured. Formalin-fixed, paraffin-embedded tissue biopsies underwent H&E staining and IHC using CD117, S-100, and calretinin. Staining patterns were semi-quantitatively evaluated. Data were recorded as frequencies and percentages. Positive and negative controls ensured IHC accuracy. Results: Most patients were under 11 months of age (52%), with a male predominance (80%). Constipation was the most common presenting symptom (48%), followed by delayed meconium passage and abdominal distension. HD accounted for 80% of diagnoses, while 20% had ARM, including subtypes like anocutaneous fistula and anorectal agenesis. On H&E of rectal HD biopsies, proximal ends showed positivity in 96.7% and distal ends were uniformly negative. In ARM cases, rectal biopsies showed 25% positivity and 75% negativity of ganglion cells. Calretinin IHC confirmed the presence of ganglion cells in proximal and distal sigmoid colon of HD cases (100%) and revealed absence in the rectum (62.5%). ARM cases showed a progressive increase in calretinin positivity from rectum to distal colon. S-100 staining revealed hypertrophic nerve fibers in 13.35% of HD rectal biopsies and 75% of ARM biopsies. CD117 immunostaining showed decreased interstitial cells of Cajal (ICCs) in HD but increased staining in ARM, aligning with previous studies indicating a possible role of ICC depletion in motility disorders. Conclusion : Although H&E staining remains the cornerstone for diagnosing HD and ARM, its limitations necessitate adjunctive methods. Calretinin IHC significantly enhances diagnostic accuracy, even in equivocal or poorly preserved samples. It aids in clear ganglion cell identification and transition zone mapping, critical for surgical planning. S-100 and CD117 further assist in evaluating nerve hypertrophy and ICC distribution, respectively. Routine incorporation of IHC, especially calretinin, alongside limited H&E sections is strongly recommended for improving diagnostic precision, optimizing treatment strategies, and ensuring better outcomes in pediatric colorectal disorders